Single-versus multiple-inhaler triple therapy in patients with COPD in Spain: a retrospective cohort study comparing adherence, persistence, risk of exacerbations and economic outcomes - González-González, M. Asunción; Pedrosa-Naudín, M. Aránzazu; Fernández-Lázaro, Diego; Planelles, Isabel Díaz; Álvarez, F. Javier; Gutiérrez-Abejón, Eduardo (Frontiers in Pharmacology, 2025)
This retrospective study aimed to compare the clinical and economic outcomes of single-inhaler triple therapy (SITT) versus multiple-inhaler triple therapy (MITT) in a large cohort of COPD patients. Metrics on adherence, prevalence, and incidence of exacerbations in COPD patients treated with SITT or MITT were analyzed using pharmacy claims data integrated with the Spanish public health database. At the 12-month follow-up, patients in the SITT cohort were significantly more adherent (75.22% vs 70.1%; OR = 1.33), more persistent (64.32% vs 52.4%; HR = 1.56) and had a lower incidence of moderate exacerbations (53.53% vs 64.07%; OR = 0.65) than patients in the MITT cohort. The main predictors associated with lack of persistence were being a naïve patient (HR = 0.55) and moderate exacerbations (HR = 0.85). Furthermore, medication costs were lower for SITT (EUR 909.31 vs EUR 1025.31), demonstrating its cost-effectiveness. Our results suggest that SITT not only may improve adherence and persistence but also contributes to a relevant reduction in the risk of moderate exacerbations. Additionally, SITT offers a more cost-effective alternative for patients with moderate to severe COPD with documented exacerbations, making it a valuable strategy in real-world clinical practice.